2022
DOI: 10.1111/inm.12973
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in people treated with long‐acting injectable antipsychotics in monotherapy or polypharmacy: a naturalistic study

Abstract: Sexual dysfunction, psychosis, and antipsychotics are known to be related, but the precise association between them is still unknown. Most evidence about the prevalence of sexual dysfunction in people treated with antipsychotic drugs comes from studies with restrictive samples. That is why our main objective was to determine the prevalence of sexual dysfunction in a real‐life sample of outpatients treated with antipsychotics, considering gender. A cross‐sectional naturalistic study was developed, including peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
1
0
0
1
Order By: Relevance
“…Higher than a study done in Northern Nigeria (40.2%), Turkey (46%), and China (60.7%) (22,35,37). Similar to studies done in Northern Nigeria (58.8%) and Spain (57.1%), this study found that 58.0% of female schizophrenia patients had sexual dysfunction (35,42,45). However, the results of study's ndings are higher than those carried out in Southwest Nigeria (42.2%) (40), but lower than those carried out in Ethiopia (78.6%), Turkey (68%), Chinese rural (82.7%), and Macdonald (92%) (10,18,22,44).…”
Section: Discussionsupporting
confidence: 58%
“…Higher than a study done in Northern Nigeria (40.2%), Turkey (46%), and China (60.7%) (22,35,37). Similar to studies done in Northern Nigeria (58.8%) and Spain (57.1%), this study found that 58.0% of female schizophrenia patients had sexual dysfunction (35,42,45). However, the results of study's ndings are higher than those carried out in Southwest Nigeria (42.2%) (40), but lower than those carried out in Ethiopia (78.6%), Turkey (68%), Chinese rural (82.7%), and Macdonald (92%) (10,18,22,44).…”
Section: Discussionsupporting
confidence: 58%
“…Metabolik profil ve buna bağlı yan etkiler paliperidon depo form ile yapılan bir çalışmada stabil iken 26 ; başka bir çalışmada ise muhtemel prolaktin yüksekliğine bağlı galaktore, amenore ve beraberinde cinsel işlevlerde bozulma gösterilmiştir 28 . Yine paliperidon depo form ile yapılan bir çalışmada; risperidon depo kullanan şizofreni hastalarının tedavisi paliperidon palmitat ile değiştirildiğinde prolaktin düzeyleri düşmüş ve cinsel yan etkiler de azalmıştır 29 . Başka bir olgu sunumunda ise; oral paliperidon tedavisi prolaktin yüksekliği sonrası değiştirilmiştir 30 .…”
Section: Discussionunclassified